Träningsintensitet hos islandshästar i ridskoleverksamhet - Tjernström, Caroline (2017)
Exercise intensity of Icelandic riding school horses In Sweden, there are a total of 9500 horses at riding schools and a hundred riding schools with Icelandic horses. These horses are performing 5 million hours under rider each year. Despite this, there are very few studies measuring training intensity of horses in riding schools. Riding school horses are commonly participating in competitions during the year. However, there are no present studies on Icelandic horses training intensity at riding schools.